Cybernetic Hive Minds: A Review - Chowdhury, Anirban; Ramadas, Rithvik (AI (Basel), 2022)
Insect swarms and migratory birds are known to exhibit something known as a hive mind, collective consciousness, and herd mentality, among others. This has inspired a whole new stream of robotics known as swarm intelligence, where small-sized robots perform tasks in coordination. The social media and smartphone revolution have helped people collectively work together and organize in their day-to-day jobs or activism. This revolution has also led to the massive spread of disinformation amplified during the COVID-19 pandemic by alt-right Neo Nazi Cults like QAnon and their counterparts from across the globe, causing increases in the spread of infection and deaths. This paper presents the case for a theoretical cybernetic hive mind to explain how existing cults like QAnon weaponize group think and carry out crimes using social media-based alternate reality games. We also showcase a framework on how cybernetic hive minds have come into existence and how the hive mind might evolve in the future. We also discuss the implications of these hive minds for the future of free will and how different malfeasant entities have utilized these technologies to cause problems and inflict harm by various forms of cyber-crimes and predict how these crimes can evolve in the future.